MAIN ASPECTS OF DEPRESSION IN RURAL TERRITORIES - Tsvihun, I.A. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
The most dangerous for a particular area are the systemic and long-term decline of its development, which leads to the creation of depressed areas. Territorial development disproportions are formed by the various affecting various factors, especially including the violations of socio-economic and environmental development. A feature of the rural areas depression is the lack of comprehensive and balanced development, which is associated with the territorial location and development of the agricultural sector. Its factors makes it difficult to assess and overcome the rural areas depression. The purpose of the article is to study the issue of depressed rural areas identification and improve the system It is established that in rural depressed areas there is a violation of economic, social, demographic, and other processes. It is noted that the goal of social development is human needs and man himself, not only economic development. The main goals of rural development are rural residents, their well-being, quality of life and favorable living environment. Therefore, the current assessment of the depression level in rural areas considers indicators that reflect the state of their development is not fully. The only indicator that reflects the living conditions of the population is the natural population growth rate. A system of indicators for assessing the rural areas depression is proposed, which is designed to assess the living conditions of the rural population of depressed areas: life expectancy of men and women, population aging rate, total fertility rate, generation replacement index. Mortality rate at the age of 15-45 years. The main condition for overcoming the rural areas depression is to determine the causes of the territory decline and assess the level of depression. Only considering the main problems of rural residents living conditions will allow to introduce measures to overcome depression